Interview with Patricia Viseur-Sellers, Legal Officer on Gender Issues - Sharratt, Sara; Viseur-Sellers, Patricia (Women & therapy, 1999)
In this interview such issues as morality and integrity, the meaning of rape in various social contexts and the demand for justice from the international community are discussed. In addition to her role in the legal system, Viseur-Sellers discusses her experiences as an African-American woman in the social systems of Europe, the United States and Latin America. The personal effects of this work on her are also explored.